2023
DOI: 10.1111/mcn.13508
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the gendered norm of eating last and mental health of newly married women in Nepal: A longitudinal study

Abstract: Eating last is a gendered cultural norm in which the youngest daughters-in-law are expected to eat last after serving others in the household, including men and in-laws. Using women's eating last as an indicator of women's status, we studied the association between eating last and women's mental health. Using four rounds of prospective cohort data of 18-25-year-old newly married women (n = 200) cohabiting with mothers-in-law between 2018 and 2020 in the Nawalparasi district of Nepal, we examined the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Also, when food insecurity is severe, the discriminatory capacity of the social norms would be minimal. Everybody gets much less than the recommended diet ( 37 ). According to the literature, adolescents with low bargaining power have less control over intrahousehold food allocation and, as a result, are more likely to have poor nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Also, when food insecurity is severe, the discriminatory capacity of the social norms would be minimal. Everybody gets much less than the recommended diet ( 37 ). According to the literature, adolescents with low bargaining power have less control over intrahousehold food allocation and, as a result, are more likely to have poor nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Our research found that this extended to eating, encouraging girls to accept that they could not eat what they pleased, they could not routinely access economic resources, and they may have to sacrifice their nutritional need for the family. This would help prepare them for life as a dutiful daughter-in-law and wife who is accustomed to being restricted in what they could eat [68].…”
Section: Surveillance Of Girlsmentioning
confidence: 99%